Quranic Arabic From its Hijazi Origins to its Classical Reading Traditions - van Putten, Marijn (Studies in Semitic Languages and Linguistics, 2022)
This work examines the history of Quranic Arabic. Using manuscript and medieval literary evidence, it uncovers the earliest Hijazi Arabic layer of the text, and describes its evolution into the Classical Arabic canonical reading traditions.; Readership: Everyone interested in the history of Arabic and the Quranic text and the early history of Classical Arabic and the Quranic reading traditions.